Bel fıtığı ameliyatı sonrası pedometre destekli yürüyüş ve tele izlemin ağrı engellilik düzeyi ve yaşam kalitesine etkisi - Aldemir, Kadriye (My University, 2019)
Amaç: Araştırmanın amacı bel fıtığı ameliyatı sonrası pedometre destekli yürüyüş ve tele izlemin ağrı, engellilik düzeyi ve yaşam kalitesine etkisini belirlemektir.Gereç ve Yöntem: Randomize kontrollü deneysel türde olan araştırma Mart 2018-Ocak 2019 tarihleri arasında bir üniversite hastanesinin beyin cerrahi kliniğinde yapıldı. Örnekleme basit rastgele yöntemiyle belirlenen ve araştırma kriterlerine uyan 80 hasta (40 deney, 40 kontrol) alındı. Çalışma sürecinde 13 hastada çıkarılma kriterleri oluştuğu için çalışma 67 (33 deney, 34 kontrol) hastayla tamamlandı. Veriler hasta tanıtım formu, McGill Ağrı ölçeği, Oswetry Engellilik ölçeği ve SF- 36 Yaşam Kalitesi Ölçeği ile toplandı. Deney grubunun günlük adım sayısı, yürüme mesafesi ve yürüme süresine ilişkin veriler araştırmacı tarafından oluşturulan yürüme çizelgesi ile elde edildi. Veriler, ameliyattan bir gün önce, ameliyattan sonra 3, 7, 11 ve 15. haftalarda yüz yüze görüşme yöntemiyle toplandı. Verilerin değerlendirilmesinde ki kare testi, eşleştirilmiş gruplar için t testi, bağımsız gruplar için t testi, Pearson korelasyon analizi kullanıldı.Bulgular: Ameliyattan 7 ve 11. haftanın sonunda grupların ağrı düzeyleri, 11 ve 15. haftanın sonunda ise engellilik düzeyleri arasındaki fark deney grubu lehine anlamlıydı (p<0,05). 15. haftanın sonunda deney grubu hastaların kontrol grubuna göre yaşam kalitesinin fiziksel rol güçlüğü, enerji ve canlılık, ruh sağlığı, sosyal işlevsellik ve ağrı alt boyut puanları anlamlı olarak daha yüksekti (p<0.05). Sonuç: Çalışma bulguları bel fıtığı ameliyatı sonrası yürümenin hastaların ağrı, engellilik düzeyleri üzerinde olumlu etkileri olduğunu ve yaşam kalitesini iyileştirdiğini gösterdi.

Aim: The study aims to determine the effect of pedometer-supported walking and tele monitoring after the herniated disk surgery on pain, disability levels and quality of lifeMaterial and Method: The study which was designed as a randomized controlled experimental design was conducted in the neurosurgery department of a university hospital between March 2018 and January 2019. 80 patients (40 experimental, 40 control) were taken as samples who were determined with simple random sampling and comply with the study criteria in order to increase the reliability of the study. Since 13 patients possessed exclusion criteria, the study was completed with 67 patients (33 experimental, 34 control). The data was collected with patient description form, McGill Pain questionnaire, Oswestry Disability index and SF-36 Quality of Life Questionnaire. The data of the number of steps, walking distance and walking duration of the experimental group was obtained with walking chart developed by the researcher. The data was collected one day after the surgery and after the 3rd, 7th, 11th and 15th weeks of the surgery with face-to-face interview method. In the evaluation of the data, Chi-square test, t-test for paired groups, t-test for independent groups and Pearson correlation coefficient were used. Findings: The difference between the pain levels of groups at the end of the 7th and 11th weeks after the surgery and the disability levels at the end of the 11th and 15th weeks of the surgery were significant in favor of experimental group (p<0.05). At the end of the 15th week, the physical role difficulty, energy and vitality, mental health, social functionality and pain sub-dimension scores of quality of life were significantly higher in the experimental group compared to control group (p<0.05). Conclusions: The findings of the study indicate that walking after herniated disk surgery had positive effects on pain and disability levels and increased the quality of life.
Keywords: ağrı; cerrahi; disability; engellilik Lumbar disc hernia; Hemşirelik; Lumbar disk herni; Nursing; pain; surgery; walking; yürüyüş